Posisi Teori I’jâz Al-Qur’ân ‘Âisyah Abdurrahmân Bintu Al-Syâthi’ dan Sumbangannya dalam Kajian Al-Qur’an - Nuril Hidayah (AN NUR: Jurnal Studi Islam, 2015)
This study is aimed at identifying Bintu al-Syâthi’s position with her theory of i’jâz al-Qur’an among another theoretician of i’jâz lugawî and her contribution toward i’jâz discourse and qur’anic studies. To achieve that goal, it will be explore some elements underlying her theory, namely the basic element, the mode of thought, the essential element, the aim and the end of her i’jâz thought